2012
DOI: 10.1001/archophthalmol.2012.1988
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Injury After Laser Hair Reduction Treatment to the Eyebrow

Abstract: 1. Kindler P. Morning glory syndrome: unusual congenital optic disk anomaly. Am J Ophthalmol. 1970;69( Peripapillary staphyloma with associated retinopathy of prematurity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 8 publications
0
32
0
1
Order By: Relevance
“…Up to the present time, the laser procedures in the vicinity of the periocular zone have been reported to be related to the risk of ocular injuries involving the sore eye, blurred vision, photophobia, damage to iris, conjunctival injection, endothelial keratic precipitates, and cells in the anterior chamber. [10][11][12][13][14][15][16][17][18] Compared the above data from CVL treatment of periorbital BCC with the rate of ocular injuries due to the facial laser procedure with other lasers, CVL treatment seems to be safer, as the use of another laser in facial cosmetic treatment is reported to be associated with ocular injury rate of 33%, χ 2 =3.515, P<0.06 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to the present time, the laser procedures in the vicinity of the periocular zone have been reported to be related to the risk of ocular injuries involving the sore eye, blurred vision, photophobia, damage to iris, conjunctival injection, endothelial keratic precipitates, and cells in the anterior chamber. [10][11][12][13][14][15][16][17][18] Compared the above data from CVL treatment of periorbital BCC with the rate of ocular injuries due to the facial laser procedure with other lasers, CVL treatment seems to be safer, as the use of another laser in facial cosmetic treatment is reported to be associated with ocular injury rate of 33%, χ 2 =3.515, P<0.06 19 .…”
Section: Discussionmentioning
confidence: 99%
“…9 Whereas some laser systems use the radiation that is not mostly absorbed by neither melanin nor oxyhemoglobin, laser light can reach the reticular layer of the dermis or even deeper to cause such ocular injuries as pain above and behind the eye, blurred vision, and photophobia. 10 Thus it seems important to adopt new modes of laser surgical treatment management of BCC located near an eye.…”
Section: Introductionmentioning
confidence: 99%
“…Ocular complications such as anisocoria, uveitis, pupillary distortion, posterior synechiae, iris atrophy, nuclear cataract, visual field defect, macular hole, and retinal scarring have been reported with Diode laser (800 nm), Alexandrite laser (755 nm), and Intense Pulsed Light (IPL) (500-1200 nm), mostly related to lack of eye protection [18][19][20][21]. Although PDL has a lower tissue penetration (wavelength of 595 nm), permanent visual impairment has also been reported [22].…”
Section: Discussionmentioning
confidence: 99%
“…All hair removal laser systems have the potential to cause ocular injuries. Few previous reports of laser‐assisted hair removal concluded that the most preventable risk factor predisposing to ocular injury was poor adherence to optical safety guidelines …”
Section: Introductionmentioning
confidence: 99%
“…Few previous reports of laser-assisted hair removal concluded that the most preventable risk factor predisposing to ocular injury was poor adherence to optical safety guidelines. [8][9][10][11][12] This study assesses the adherence of dermatologists and nurses to optical safety guidelines, and identifies other factors that may make the eye more vulnerable to injury while administering the laser treatment.…”
mentioning
confidence: 99%